Early Events of the Reaction Elicited by CSF-470 Melanoma Vaccine Plus Adjuvants: An In Vitro Analysis of Immune Recruitment and Cytokine Release - Pampena, María B.; Barrio, María M.; Juliá, Estefanía P.; Blanco, Paula A.; von Euw, Erika M.; Mordoh, José; Levy, Estrella Mariel (Frontiers in Immunology, 2017)
In a previous work, we showed that CSF-470 vaccine plus BCG and GM-CSF as adjuvants resulted in a significant benefit in the distant metastasis-free survival when comparing vaccinated vs IFN-α2b-treated high-risk cutaneous melanoma patients in a phase II study. Immune monitoring demonstrated an increase in anti-tumor innate and adaptive immunity of vaccinated patients, with a striking increase in IFN-γ secreting lymphocytes specific for melanoma antigens. In an effort to dissect the first steps of the immune response elicited by CSF-470 vaccine plus adjuvants, we evaluated, in an in vitro model, leukocyte migration, cytokine production and monocyte phagocytosis of vaccine cells. Our results demonstrate that leukocytes recruitment, mostly from the innate immune system, is an early event after CSF-470 vaccine plus BCG plus GM-CSF interaction with immune cells, possibly explained by the high expression of CCL2/MCP-1 and other chemokines by vaccine cells. Early release of TNF-α and IL-1β pro-inflammatory cytokines and efficient tumor antigens phagocytosis by monocytes take place and would probably create a favorable context for antigen processing and presentation. Although the presence of the vaccine cells hampered cytokines production stimulated by BCG in a mechanism partially mediated by TGF-β and IL-10, still significant levels of TNF-α and IL-1β could be detected. Thus, BCG was required to induce local inflammation in the presence of CSF-470 vaccine cells.